Income Expansion and Contraction: A Diagrammatic Representation - Lerner, Joseph (Quarterly Journal of Economics, 1951)
Journal Article Income Expansion and Contraction: A Diagrammatic Representation Get access Joseph Lebner Joseph Lebner Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 65, Issue 1, February 1951, Pages 138–141, https://doi.org/10.2307/1879506 Published: 01 February 1951